'A Sudden Surprise of the Soul': Wonder in Museums and Early Modern Philosophy. (14th October 2016) - Lord, Beth
Abstract: Recent museum practice has seen a return to 'wonder' as a governing principle for display and visitor engagement. Wonder has long been a contentious topic in aesthetics, literary studies, and philosophy of religion, but its adoption in the museum world has been predominantly uncritical. Here I will suggest that museums draw on a concept of wonder that is largely unchanged from seventeenth-century philosophy, yet without taking account of early modern doubts about wonder's efficacy for knowledge. In this paper I look at Descartes' and Spinoza's views about wonder and the uses and disadvantages of wonder as a learning tool. This examination is extended to consider Descartes' and Spinoza's likely views about 'museums', in the sense of spaces that link objects both to feeling and to knowing. Finally, I suggest that there are resources in Spinoza's philosophy for bringing knowledge-enhancing feelings into the museum without resorting to the problematic concept of wonder.